THE INFLUENCE OF INDONESIAN NAVY DIPLOMACY THROUGH NAVAL PRESENCE ON THE EFFECTIVENESS OF MARITIME OPERATIONS IN THE NORTH NATUNA SEA - Amarulla Octavian; Priyo Cahyono; Widodo Setiyo Pranowo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
The North Natuna Sea is still a hot topic of discussion both nationally, regionally and internationally. The discussion is inseparable from the interest in the potential of natural resources and energy contained therein. The problems with the boundaries of the Indonesian Exclusive Economic Zone (ZEEI) and the territorial claims in the South China Sea (SCS) by China make this problem more complex so that it is necessary to immediately get serious handling to prevent risks and losses for the national interest. The presence of elements of the naval presence in the North Natuna Sea is a form of handling in the field of maritime operations which aims to maintain maritime security and protect the sovereignty of the Unitary State of the Republic of Indonesia (NKRI) from various threats. Through this article, I would like to provide an overview of Indonesian Navy diplomacy through its naval presence in the North Natuna Sea and its influence on the effectiveness of maritime operations carried out based on the results of research using quantitative methods. Naval presence is part of the Indonesian Navy's diplomacy in dealing with the problems that occur as well as an effort to maintain world recognition of the Republic of Indonesia. Keywords : effectiveness; the presence of elements of the Indonesian Navy, North Natuna Sea; maritime operations